2008
DOI: 10.1007/s00384-008-0616-8
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of metabolic response to preoperative radiochemotherapy in locally advanced rectal cancer measured by PET/CT

Abstract: Metabolic response to a preoperative RCTX using FDG-PET/CT in rectal cancer patients can be correlated with histopathological response, but FDG uptake of peritumoral inflammation cells limited the results and led to false negative results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
75
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 26 publications
1
75
2
Order By: Relevance
“…Recent studies mainly investigated the relationships of the changes of SUV after treatment and pathologic response in various tumors including NSCLC [6,[24][25][26]. However, these studies also investigated the primary tumor SUV values effect on prognosis and whether the changes of SUV values after treatment could predict pathologic response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies mainly investigated the relationships of the changes of SUV after treatment and pathologic response in various tumors including NSCLC [6,[24][25][26]. However, these studies also investigated the primary tumor SUV values effect on prognosis and whether the changes of SUV values after treatment could predict pathologic response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As reported earlier (15), the inclusion criteria were biopsyproven rectal adenocarcinoma between 0 and 15 cm from the anal verge, an endosonographic tumor stage of uT3 with or without local lymph node metastases, no distant metastases, no previous chemotherapy or radiation therapy, a Karnofsky index of more than 60%, and normal liver and kidney function. The exclusion criteria were a history of other malignancies, diabetes mellitus, lack of compliance, and contraindications to nRCT.…”
Section: Patient Population and Treatmentmentioning
confidence: 99%
“…Standardized uptake value (SUV) analysis of this patient population for response assessment was published in previous articles (15,17).…”
Section: Patient Population and Treatmentmentioning
confidence: 99%
“…Many investigators have reported a substantial decrease in standardised uptake value (SUV) post-CRT in responders compared with nonresponders [19][20][21][22]. However, only a few studies have compared the abilities of MRI and PET/CT to enable prediction of responses to neoadjuvant CRT [23,24].…”
mentioning
confidence: 99%